Helping oxytocin deliver: considerations in the development of oxytocin-based therapeutics for brain disorders - Macdonald, Kai; Feifel, David (Frontiers in Neuroscience, 2013)
Concerns regarding a drought in psychopharmacology have risen from many quarters. From one perspective, the wellspring of bedrock medications for anxiety disorders, depression, and schizophrenia was serendipitously discovered over thirty year ago, the swell of pharmaceutical investment in drug discovery has receded, and the pipeline’s flow of medications with unique mechanisms of action (i.e. glutamatergic agents, CRF antagonists) has slowed to a trickle. Might oxytocin (OT)-based therapeutics be an oasis? Though a large basic science literature and a slowly increasing number of studies in human diseases support this hope, the bulk of extant OT studies in humans are single-dose studies on normals, and do not directly relate to improvements in human brain-based diseases. Instead, these studies have left us with a field pregnant with therapeutic possibilities, but barren of definitive treatments. In this clinically-oriented review, we discuss the extant OT literature with an eye toward helping OT deliver on its promise as a therapeutic agent. To this end, we identify ten key questions that we believe future OT research should address. From this overview, several conclusions are clear: 1) the OT system represents an extremely promising target for novel CNS drug development; 2) there is a pressing need for rigorous, randomized controlled clinical trials targeting actual patients; and 3) in order to inform the design and execution of these vital trials, we need further translational studies addressing the questions posed in this review. Looking forward, we extend a cautious hope that the next decade of OT research will birth oxytocin-targetted therapeutics that can truly deliver on this system’s therapeutic potential.